(untitled) (Movimenta (ISSN 1984-4298), 2022)
Individual differences of personality are thought to influence motor performance. In terms of cortical arousal levels, because extraverts are infra-activated and introverts are hyper-activated, environment stimuli might enhance the impact of the extraversion trait on task performance. This study investigated the effect of light and sound noise on the swimming performance of extraverted and introverted children. 19 extraverts (12 boys, 7 girls) and 22 introverts (12 boys, 10 girls), ages 8.2 ± 0.9 years, adapted to water and swimming at intermediate levels. Participants performed two trials of the task (swimming 15 meters as fast as possible in crawl style) under two environment conditions: bright light/loud noise (A) and dim light/slight noise (B). Movements were filmed to allow calculation of time to complete the task and the stroke cycle. There was a significant effect for the group factor, with extraverts swimming faster than introverts. No effect was detected for the environment factor or the interaction group/environment. Regarding stroke cycle, no differences were found for group, environment or interaction. Although extraversion has not affected mechanical aspects of crawl style, compared to introverts, extraverts swan faster, showing a more effective process of reacting and executing movements in time-constraints tasks.